The practice of misuse : rugged consumerism in contemporary American culture - Malewitz, Raymond (Stanford, California : Stanford University Press, 2014)
This title examines the oppositional emergence and eventual ideological containment of 'rugged consumers' in late 20th century American literature, who creatively misuse, reuse, and repurpose the objects within their environments to suit their idiosyncratic needs and desires. The book shows how certain authors position their rugged consumers within the intertwined American myths of primal nature and rugged individualism, creating left- and right-libertarian maker communities that are sceptical of both traditional political institutions and (in its pre-neoliberal state) globalised corporate capitalism.
Misuse : from aesthetics to practice -- Theaters of rugged consumerism -- The garden in the machine : biomimetic hybrids and the tragedy of singular use -- The rugged consumer Bildungsroman -- Ritual, play, and neoliberal rugged consumerism -- The commodity at the end of the world.
Includes bibliographical references (p. 209-220) and index.
Keywords: American literature -- 20th century -- History and criticism; Consumption (Economics) in literature; Material culture in literature; Consumption (Economics) -- United States; Material culture -- United States